Influence of platelet antigens differences between donor and recipient on neutropenia and thrombocytopenia duration after allogeneic stem cell transplantation - L. L. Golovkina; R. M. Kutyina (Онкогематология, 2022)
Purpose: to study influence of platelet antigens system (HPA — Human Platelet Antigens) differences between donor and recipient on neutropenia and trombocytopenia duration after hematopoietic stem cells transplantation (HSCT).Materials and methods: 40 patients at the age from 19 till 55 years (a median age ~ 28.5) after allogeneic HSCT from HLA-identical sibling are included in the study. For the majority of patients (94%) a source of haematopoetic stem cells (HSC) were a bone marrow. 28 patients received myeloablative conditioning regimens and 12 patients — a lowered intensity conditioning. Achievement of 0.5×109/l or more considered as beginning of neutrophil count recovery. As the beginning of platelet count recovery considered achievement value of 50×109/l after platelet transfusions stopping. Identification of eight allele ≪a≫ and ≪b≫ genes HPA-1,-2,-3 and-5 locuses performed by polymerase chain reaction (PCR) with use allele-specific primers. Serological HlAtyping performed by microlymphocytotoxic test with use of specific serum panels.Results: the basic criterion of patient groups distribution (HPA-identical — 1st group; HPA-compatible — 2nd group; HPA-incompatible — 3rd group) was identity or qualitative characteristic of their differences with donor for HPA-genes. Earlier neutrophils and platelet counts recovery in patients transplanted from HPA-identical/compatible donor in comparison with patients with HPA-incompatible transplant, it is shown. In first two groups neutropenia duration was 13.45 and 14.3 days, respectively; in 3 groups — 19.0 days. This pattern of recovery was shown irrespective of conditioning regimens and leukemia type. Platelet recovery occurred earlier in patients of 1st (16.22 days) and 2nd groups (18.2 days) in comparison with patients of 3rd groups (24.2 days).Conclusion: HPA-incompatibility can influence neutrophils and platelet recovery duration after allogeneic HSCT.